Effects of simvastatin on bone regeneration in the mandibles of ovariectomized rats and on blood cholesterol levels. - Junqueira, Juliana Campos [UNESP]; Mancini, Maria N G; Carvalho, Yasmin R; Anbinder, Ana Lia; Balducci, Ivan; Rocha, Rosilene F (Nihon University School of Dentistry, 2002)
The purpose of this study was to evaluate the effects of simvastatin on guided bone regeneration in the mandibles of ovariectomized rats, and to observe their blood cholesterol levels. Seventy female rats were divided into two groups: control and treated, both groups containing normal and ovariectomized rats. A month after ovariectomy a bone defect was created in the mandible, and was covered by a polytetrafluoroethylene membrane. The treated groups received simvastatin orally for 15 or 30 days. The rats were sacrificed 15, 30 or 60 days after surgery, at which time a blood sample was extracted for blood cholesterol level analysis and the mandible was extracted for densitometric, histological and morphometric analysis. All specimens underwent analysis of variance. The ovariectomized animals had higher cholesterol levels than the treated normal animals, and no significant difference was found between the different treatment periods and the sacrifice times. The densitometric, histological and morphometric analysis showed that the treated ovariectomized animals developed more new bone than the control ovariectomized rats, but no significant difference was observed between the treatment periods. It can be concluded that the deficiency of estrogen increased the level of blood cholesterol and that the simvastatin aided new bone formation in the ovariectomized animals.
Keywords: cholesterol; hydroxymethylglutaryl coenzyme A reductase inhibitor; hypocholesterolemic agent; politef; simvastatin; analysis of variance; animal; artificial membrane; blood; bone density; bone regeneration; drug effect; female; jaw disease; mandible; ovariectomy; pathology; radiodensitometry; rat; statistics; tissue regeneration; Wistar rat; Analysis of Variance; Animals; Anticholesteremic Agents; Bone Density; Bone Regeneration; Cholesterol; Densitometry, X-Ray; Female; Guided Tissue Regeneration; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Mandible; Mandibular Diseases; Membranes, Artificial; Ovariectomy; Polytetrafluoroethylene; Rats; Rats, Wistar; Simvastatin; Statistics